(3ZQaI GdeYdeGJ (B:s (3eLehYI bUUjI (B/s - (3GdYHdGfj, ehVj eMeOs ([(3ecGf GdfTQ ZjQ eMOO(B] :s (3GdJaQO dNOeGJ GdJUeje hfTQ GdeWHhYGJ,s, 2022)
(3JbOe GdeDdag ehVj eMeO GdYHdGfj, aj cJGHgG GdPj Med YfhGf (B"(3ZQaI GdeYdeGJ (B: (3eLehYI bUUjI(B" (3YOI bUU aj bGdH ebGdj, hJbOe fUhU CNQi JMed YOI bhGdH COHjI, hGSJYGfJ HcKjQ ef GdThGgO dMceGA hadGSaI(B. (3LejY fUhU gPg GdeLehYI JOGNdJ ajgG GdBeGd eY GdCMdGe, hGdMjGI eY GdehJ, hGdaQMI eY GdNjHI, ajgG eaGQbGJ hCMOGK hehGba(B.s
(3GdbUI GdbUjQI(B.s
(3JUeje hENQGL (B: (3JQfOj ZQGajcS dNOeGJ GdJUeje Gdafj(B.s
Keywords: (3GdbUU GdYQHjI GdbUjQIs -- (3bQf (B21s; (3GdCOH GdYQHjs -- (3bQf (B21s